Immune Response, Viral Shedding Time, and Clinical Characterization in COVID-19 Patients With Gastrointestinal Symptoms - Yang, Huan; Xi, Xiangyu; Wang, Weimin; Gu, Bing (Frontiers in Medicine, 2021)
Background and Aims: Gastrointestinal (GI) symptoms are frequently observed in coronavirus disease (COVID-19) symptoms. Previous studies have mainly focused on epidemiology and characteristics in patients with GI symptoms, little is known about the roles of the immune response in susceptibility to and severity of infection. Here, we analyzed COVID-19 cases to determine immune response and clinical characteristics in COVID-19 patients with GI symptoms. Methods: Based on the presence of GI symptoms, 79 patients in Xuzhou were divided into GI and non-GI groups. A retrospective study investigating the clinical characteristics, selected laboratory abnormalities, immune response, treatment, and clinical outcome was performed to compare patients with or without GI symptoms. Results: Approximately 25% of patients reported at least one GI symptom. Our results showed significantly higher rates of fatigue, increased LDH, increased CK, higher percentage increase neutrophil-to-lymphocyte ratio (NLR), lymphopenia, and bilateral pneumonia in patients with GI symptoms. No significant changes in serum amylase (SAA), immunoglobulin (Ig) G, IgM, C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6), viral shedding time, liver injury, and kidney injury between the two groups were observed. The clinical type on admission of patients with GI symptoms reported significantly higher rates of critical disease type (20 vs. 3.3%; p = 0.033). However, the survival rate did not differ between the two groups. Conclusions: Increase in total lymphocytes and NLR as well as the elevation of CRP, SAA, PCT, IL-6, CK, and LDH were closely associated with COVID-19 with GI symptoms, implying reliable indicators COVID-19 patients with GI symptoms were more likely to develop into a severe disease.